Microgel Additives for Aqueous Lubrication: Tailoring Friction and Wear via Composition and Thermal Responsiveness - Syed, Junaid; Dyck, Florian; Herberg, Artjom; Kuckling, Dirk; Gosvami, Nitya Nand (Advanced Engineering Materials)
The tribological behavior of thermo‐responsive poly(N‐isopropylacrylamide) (PNIPAAm)‐based microgels is investigated for use as water‐dispersible lubricant additives. Two types of microgels are synthesized using a surfactant‐free emulsion polymerization method: MG0, consisting of pure PNIPAAm with a volume phase transition temperature (VPTT) of ≈33 °C, and MG16, consisting of PNIPAAm copolymerized with hydrophobic tert‐butyl acrylamide, exhibiting a lower VPTT of around 23 °C. Swelling and lubrication performance are evaluated at 20 and 40 °C. Both microgels significantly reduce friction and wear compared to water alone. At 20 °C, MG0 remains fully swollen and provides effective wear protection through hydrated microgel lubrication. MG16, being near its VPTT, exhibits partial collapse and slightly higher wear. At 40 °C, MG16 demonstrates improved wear resistance, attributed to enhanced film compaction in the collapsed state. Raman spectroscopy and scanning electron microscopy–energy‐dispersive X‐ray spectroscopy confirm that carbon‐rich tribofilms are formed via tribochemical reactions. MG0 produces more graphitic films, while MG16 generates amorphous carbon structures. These findings highlight the tunability of microgel composition for designing adaptive, water‐based lubricants for temperature‐sensitive applications.

Experimental Dataset: Force and Displacement Measurements of Four Rubber-Metal Bushing Types from a Passenger Car under Harmonic Displacement Excitation - Schütte, Jan
This dataset contains experimental measurements of the radial dynamic and quasi-static characteristics of four different types of Rubber-Metal Bushings (RMBs) used in the suspension system of a passenger car under harmonic displacement excitation. For each bushing type, 2–3 individual specimens were tested. Quasi-static measurements were performed at a constant excitation frequency of 0.05 Hz with varying displacement amplitudes. Dynamic measurements were conducted with displacement amplitudes ranging from 0.04 mm to 0.3 mm and excitation frequencies of 2, 5, 10, ..., up to 100 Hz. The data is structured by bushing type, measurement mode, amplitude, and frequency, and is provided in *.csv and *.hrm format. It is intended to support further research in modeling rubber-metal bushings and parameter identification techniques.
Keywords: bushing; experimental data; rubber-metal-bushing; Dataset suspension

The Amelia Project - Episode 87 - King Arthur (537 AD) - Ulsberg Brager, Oystein; Thorne, Philip; Freudinger, Markus
"He came concealed, but he hath now revealed his true identity! Kneel for the mighty King Arthur!" The Amelia Project is a production of Imploding Fictions. This episode featured Alan Burgon as The Interviewer, Hemi Yeroham as Kozlowski, Owen Lindsay as Big Jim, Patrick Lamb as Gavin, Anne Weiner as the barmaid, Anne Marie Sheridan, Beus Lunaire, Lara Bozkurt, Nicola Ségur and Torgny G. Aanderaa as villagers, Jordan Cobb as Jackie Williams and Erin King as Mia Fox. The episode was written by Oystein Ulsberg Brager with story and audio editing by Philip Thorne, translations into Old English by Dr. Markus Freudinger, sound design by Eli Hamada Mcilveen, music by Fredrik Baden, graphic design by Anders Pedersen, production assistance by Maty Parzival, and casting assistance by Julia C. Thorne. The episode was recorded at RedP studio in Vienna, with engineering by Arpad Hadnagy and Oliver Illes and assistance by Paul Kraner. Website: https://ameliapodcast.com/ Transcripts: https://ameliapodcast.com/season-5

Mathematikbezogenes Wissen, Einstellungen und Lerngelegenheiten als Einflussfaktoren der situativen Beobachtung und Wahrnehmung angehender frühpädagogischer Fachkräfte - Quack, Carolin; Bruns, Julia (Frühe Bildung)

Polymer Suspensions under Uniaxial Extension – A novel Way to Produce Core-Shell-Particles? - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Stärkung sprachlicher Teilhabe durch sprachbildende Praxisanleitung - Hinweise für die Pflegeausbildung aus der Empirie. - Daase, Andrea; Darmann-Finck, Ingrid; Niederhaus, Constanze (Sprache(n) im Beruf: Gestaltung und Förderung beruflicher Sprachbildung an den ver-schiedenen Lernorten)

Menschenmengen extra und intra muros: Die Rolle der Stadtgemeinschaften bei den Gewalttaten des Hirtenkreuzzugs und der Rintfleisch-Verfolgungen - Mersch, Katharina Ulrike (Religiöse Gewalt in historischer Dimension)

Enabling Android Application Monitoring by Characterizing Security-Critical Code Fragments - Eikerling, Hendrik; Kampkötter, Anemone (Lecture Notes in Computer Science)

Das DSSZ-Modul in Nordrhein-Westfalen. Eine Umfrage zu Strukturen, Lehrinhalten und Perspektiven von Hochschullehrenden - Berkel-Otto, Lisa; Heine, Lena; Niederhaus, Constanze; Decker, Lena (Herausforderung Lehrer*innenbildung - Zeitschrift Zur Konzeption, Gestaltung Und Diskussion (HLZ))
Der Beitrag beschäftigt sich mit Hochschullehrenden und ihrem Lehrangebot im nordrhein-westfälischen Modul Deutsch für Schüler*innen mit Zuwanderungsgeschichte (DSSZ) im Lehramtsstudium. In einer Fragebogenstudie mit N = 10 Modulverantwortlichen sowie N = 46 Lehrenden im Modul werden die aktuelle Modulstrukturierung, Hintergründe der Lehrenden, ihre Sicht auf das Modul sowie Veranstaltungsinhalte erhoben. Es zeigt sich, dass das Modul in Bezug auf seine Verortung, den Umfang und seine Lehrenden sehr heterogen ist. Dennoch behandelt der Großteil der Lehrenden sehr ähnliche Inhalte in den Modulveranstaltungen. Weiterhin bilden sich in den Themen und Handlungen sehr deutlich zwei Modulschwerpunkte ab: sprachbildender Fachunterricht und DaZ-Unterricht mit neuzugwanderten Schüler*innen. Basierend auf den Ergebnissen stellt sich vor allem die Frage, wie im Rahmen des Studiums mehr Lerngelegenheiten in diesen Themenfeldern geschaffen werden können.

Assessing solids conveying in injection moulding machines using coupled numerical simulations based on the discrete element method (DEM) and multibody systems (MBS) - Landgräber, Jan; Schöppner, Volker; Brüning, Florian (International Polymer Processing)
Abstract Design of single screw machines for polymer processing often focuses on the melt dominated areas of the screw. However, solids conveying is a key aspect for processes with high screw speeds, grooved feed sections, small screw diameters and material with low bulk density. In injection moulding, throughput limitations are highly relevant in packaging applications as due to low cooling times, plasticizing affects the cycle time. In addition, insufficient solids conveying is a primary cause for air residues in the melt and final product. Therefore, well-designed feed sections are required, especially as direct processing of regrind in recycling applications becomes more relevant due to governmental restrictions. Existing models for injection moulding are based on analytical equations and do not allow to assess new feed sections and feed opening designs, adapted to high screw speeds or regrind. In this paper, numerical simulations based on the Discrete Element Method (DEM), previously used in the field of extrusion, are carried out. In order to replicate the cyclic, superimposed rotation and translation of the screw, a coupled approach of DEM and Multibody Systems Simulation (MBS) is pursued. To verify the accuracy of such coupled simulations, a special test setup is added to a conventional injection moulding machine. Pure solids conveying is investigated, as DEM does not accommodate for large plastic deformations or melting. Different screw and intake designs as well as smooth and grooved barrels are investigated. Selected resins, pellet shapes and regrind are processed, varying the processing parameters and comparing the results to the simulation. The coupled approach replicates reality well in terms of throughput, confirming that DEM can be utilised to further investigate process phenomena and develop calculation models for solids conveying in injection moulding.

Discrete element method in polymer processing – Method for development of material models - Landgräber, Jan; Brüning, Florian (Advanced Powder Technology)

Den Schein werfen/wahren. Transdiziplinaritäten und Popkulturforschungen. Ein Übersetzungsraum als Partitur - Flath, Beate; Jacke, Christoph; Schroeter-Wittke, Harald (Transdisziplinäre Räume in den Kulturwissenschaften)

Visualizing Privacy-Relevant Data Flows in Android Applications - Khedkar, Mugdha; Schlichtig, Michael; Mohan, Santhosh; Bodden, Eric (arXiv:2503.16640)
Android applications collecting data from users must protect it according to the current legal frameworks. Such data protection has become even more important since in 2018 the European Union rolled out the General Data Protection Regulation (GDPR). Since app developers are not legal experts, they find it difficult to integrate privacy-aware practices into source code development. Despite these legal obligations, developers have limited tool support to reason about data protection throughout their app development process. This paper explores the use of static program slicing and software visualization to analyze privacy-relevant data flows in Android apps. We introduce SliceViz, a web tool that analyzes an Android app by slicing all privacy-relevant data sources detected in the source code on the back-end. It then helps developers by visualizing these privacy-relevant program slices. We conducted a user study with 12 participants demonstrating that SliceViz effectively aids developers in identifying privacy-relevant properties in Android apps. Our findings indicate that program slicing can be employed to identify and reason about privacy-relevant data flows in Android applications. With further usability improvements, developers can be better equipped to handle privacy-sensitive information.

Pop-Ikonen. Kulturwissenschaftliche Zugänge. - Jacke, Christoph; Schroeter-Wittke, Harald (Popmix, POPkultur und Religion: The Next Generation)

Die drei Rollen der Star-Figur. Sarah Connors Abrechnung. - Jacke, Christoph (POP. Kultur & Kritik)
Keywords: Stars; Sarah Connor; Rollen; Qualitätsjournalismus; Boulevard; Fans

Impact of felt obligation and perceived mutual reciprocity on support between mothers and their adult children - Schoenert, Kathrin; Sommer, Sabrina; Buhl, Heike M. (Frontiers in Developmental Psychology)
Support is a vital resource at every stage of development throughout the lifespan. In the mother-child relationship, the exchange of support is subject to change in relation to the tasks and framework conditions of the current phase of life. While values and norms typically include social expectations, attitudes summarize individual thoughts or feelings. During young adulthood and midlife, attitudes are particularly important for the mutual support between mothers and their adult children when there are no practical framework conditions, such as care needs, that necessitate support. This study uses social exchange theory to examine the mediating role of felt obligation and perceived mutual reciprocity as important attitudes in the well-known relation between mothers and their adult children receiving and giving support. The sample consisted of 598 German adults (aged 20–49, 55.2% female) and 577 mothers (aged 40–87) of these adults; both perspectives were taken into account. The results from the parallel mediation analyses, in which instrumental and emotional support were considered separately, showed a mediating effect of felt obligation on the instrumental support of adult children for their mothers. The emotional support received and given by the adults to their mothers was mediated by felt obligation and perceived mutual reciprocity. The received and given instrumental and emotional support of the mothers to their adult children was mediated by perceived mutual reciprocity. The relevance of the adults' and mothers' different attitudes regarding support later in life is discussed.

The Influence of an Immersive-Collaborative Learning Unit on the Technology Acceptance of 5G and AR of Industrial Mechanic Students - Schäfers, Johannes; Temmen, Katrin (Proceedings of the 27th International Conference on Interactive Collaborative Learning (ICL2024), Volume 4)
Despite its status as a key enabling technology, the adoption of 5G in industry remains limited, mainly due to a lack of expertise, which can be addressed by incorporating 5G training into vocational schools. Since Augmented Reality (AR) faces similar challenges, it is used as the 5G application. This research aims to determine the extent to which a learning unit using 5G and AR for collaborative work can increase the intention to use these technologies in the vocational setting and gathers the factors that make up 5G acceptance. It is based on the Technology Acceptance Model 2 (TAM2). The sample includes 23 industrial mechanics students who participated in the developed learning unit. All items are scored on seven-tiered Likert scales (0 “totally disagree”; 6 “totally agree”). The results showed a non-significant change in behavioural intention to use 5G, with a mean of 4.95 (SD: 1.18) for the pre-test and 4.43 (SD: 1.68) for the posttest. The change in intention to use AR did not change significantly either, from 3.12 (SD: 1.38) at pre-test to 3.37 (SD: 1.16) at post-test. The factors Perceived Usefulness, Image, and Relevance had the lowest mean scores, indicating areas for targeted improvement. The significant change in Output Quality ratings is likely to reflect initial overestimation by students. The difference in Behavioural Intentions between 5G and AR suggests that AR may not be an effective technology for increasing 5G adoption in educational contexts. One recommendation is to address 5G in the learning unit not only indirectly.
Keywords: 5G; Key Technology; TAM · Augmented Reality; VET

Mg dopants in lithium niobate: Defect models and impact on domain inversion - Bocchini, Adriana; Rüsing, Michael; Bollmers, Laura; Lengeling, Sebastian; Mues, Philipp; Padberg, Laura; Gerstmann, Uwe; Silberhorn, Christine; Eigner, Christof; Schmidt, Wolf Gero (Physical Review Materials)

Inconsistency Handling in DatalogMTL - Bienvenu, Meghyn; Bourgaux, Camille; Khodadaditaghanaki, Atefe (Proceedings of the Thirty-Fourth International Joint Conference on Artificial Intelligence, IJCAI-25)

Vom Prompt zur Praxis – Kooperatives Seminarkonzept zur KI-gestützten Unterrichtsentwicklung in der gewerblich-technischen Lehramtsausbildung - Schäfers, Johannes; Vernholz, Mats; Jonas-Ahrend, Gabriela; Temmen, Katrin